2015
DOI: 10.1007/s10549-015-3406-3
|View full text |Cite
|
Sign up to set email alerts
|

Markers of progression in early-stage invasive breast cancer: a predictive immunohistochemical panel algorithm for distant recurrence risk stratification

Abstract: Accurate distant metastasis (DM) prediction is critical for risk stratification and effective treatment decisions in breast cancer (BC). Many prognostic markers/models based on tissue marker studies are continually emerging using conventional statistical approaches analysing complex/dimensional data association with DM/poor prognosis. However, few of them have fulfilled satisfactory evidences for clinical application. This study aimed at building DM risk assessment algorithm for BC patients.A well-characterise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
(31 reference statements)
1
13
1
Order By: Relevance
“…Most notably, we have found that Tomm34 associates with poor survival of patients with p53-mutant ovarian cancers. These data are also comparable to the findings that Tomm34 is a marker of poor outcome and a predictor of distant metastasis in breast cancer [22,23]. Thus, as with breast cancer patients, The mechanism for high level expression of Tomm34 is unclear from our studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most notably, we have found that Tomm34 associates with poor survival of patients with p53-mutant ovarian cancers. These data are also comparable to the findings that Tomm34 is a marker of poor outcome and a predictor of distant metastasis in breast cancer [22,23]. Thus, as with breast cancer patients, The mechanism for high level expression of Tomm34 is unclear from our studies.…”
Section: Discussionsupporting
confidence: 88%
“…Subsequent studies have shown that Tomm34 interacts with both Hsp70 and Hsp90 and modifies their protein folding activities [16][17][18][19][20]. In cancer, high levels of Tomm34 have been reported in bladder, colorectal and breast cancers compared to their normal tissue counterparts [21][22][23][24][25][26]. In these cancers, Tomm34 promotes colorectal cancer cell growth [21] and is a biomarker of poor outcome in early invasive breast cancer [22] and bladder cancer [26].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the clinical scenario of breast tumours, the Walker 256 cell line expressed genes of several prognostic/therapeutic/invasiveness markers of breast cancer, while some of the common genes were absent (genes were considered to be above the noise level only if the read count was ≥ 10; so gene count < 10 might be considered to be noise, and hence the corresponding gene is considered to be absent) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…BCL2 expression has been associated with prognostication of disease-free survival, overall survival, and recurrence in BC 7178. Moreover, normal breast tissue from women with BC was reported to display higher levels of BCL2 expression than breast tissue from women with no evidence of cancer 79.…”
Section: Discussionmentioning
confidence: 99%